Pengaruh Mutasi Karyawan Terhadap Prestasi Kerja Pada Badan Pemeriksa Keuangan (BPK) Perwakilan Provinsi D.I. Yogyakarta - Sugeng Sudiantoro (Universitas Muhammadiyah Yogyakarta, 2014)
This study aimed to examine the effect of mutations on work performance of employees at the Badan Pemeriksa Keuangan (BPK) Provincial Representative D.I. Yogyakarta. The samples in this study were all functional non educational employees who work in Badan Pemeriksa Keuangan (BPK) Provincial Representative D.I. Yogyakarta, which amounted to 51 employees. The sampling technique using census method whereby all existing employees into the sample amounted to 51 people. The analytical tool used in this study is multiple linear regression. The results of the analysis indicate the presence of four findings. 1)The variable of mutation had positive significant effect toward the variable of employee motivation. 2) Variable of mutation had positive significant effect toward the variable of employee performance. 3) Variable of employee motivation had positive significant effect toward the variable of employee performance, and 4) Variable of employee motivation does not mediate the effect of the implementation of variable mutation toward the variable of employee performance.Keywords : Mutation, Motivation, Work Performance.